Determining the optimum irrigation schedule in furrow‐irrigated cotton using soil moisture sensors. Issue 6 (14th November 2019) - Plumblee, Michael T.; Dodds, Darrin M.; Krutz, L. Jason; Catchot, Angus L.; Irby, J. Trenton; Jenkins, Johnie N.
Abstract : The Mississippi River Valley Alluvial Aquifer is declining at a rapid rate due to withdrawal for agricultural irrigation. This research was conducted to develop a sensor‐based irrigation threshold for cotton that maximizes net returns and irrigation water use efficiency. Earn 1 CEU in Soil & Water Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/727 .